ENCOURAGING THE GROWTH OF SKILLS AND INNOVATION IN THE NETHERLANDS - Frans Pennings (Zbornik Pravnog Fakulteta Sveučilišta u Rijeci, 2018)
This paper describes an example of best practice in the Netherlands with respect to promoting the innovation of enterprises. This policy consists of promoting cooperation between knowledge centres (including universities) and enterprises, enabling the enterprises and start-ups to be located in the neighbourhood of knowledge centres and assisting them in obtaining the required permits, and, if necessary, grant subsidies. This policy has proved to be very successful. Developing a training policy for all sectors of economy, on the other hand, is more difficult. This becomes even more difficult if employers and employees have opposite interests, especially if employers fear that the newly trained worker will leave their job after acquiring the new qualification or if the worker has to reimburse the subsidy. Therefore, the establishment of training funds, made available for all employers and workers who want to qualify for another job, can contribute to the growth of skills.